Efficacy and safety of guselkumab in patients with psoriasis who have an inadequate response to ustekinumab: results of the randomized, double‐blind, phase III NAVIGATE trial. (1st January 2018) - Langley, R.G.; Tsai, T.‐F.; Flavin, S.; Song, M.; Randazzo, B.; Wasfi, Y.; Jiang, J.; Li, S.; Puig, L.
Summary: Background: Guselkumab, an anti‐interleukin‐23 monoclonal antibody, has demonstrated significant efficacy in phase III psoriasis trials. Objectives: To evaluate the efficacy and safety of guselkumab in patients with moderate‐to‐severe plaque psoriasis who had an inadequate response to ustekinumab. Methods: In this phase III, randomized, double‐blind study, 871 patients received open‐label ustekinumab (45 mg or 90 mg) at weeks 0 and 4. At week 16, 268 patients with an inadequate response to ustekinumab [Investigator's Global Assessment (IGA) ≥ 2] were randomized (double‐blind) to guselkumab 100 mg or to continue ustekinumab; 585 of 871 patients (67%) with IGA 0/1 at week 16 continued open‐label ustekinumab. The primary end point was the number of visits at which randomized patients achieved IGA 0/1 and at least a two‐grade improvement (from week 16) from week 28 to week 40. Improvement ≥ 90% or 100% in Psoriasis Area and Severity Index (PASI 90/100) and Dermatology Life Quality Index (DLQI) of 0/1 were also assessed. Results: The mean number of visits at which patients achieved IGA 0/1 and at least a two‐grade improvemen (week 28–40) was significantly greater in the guselkumab group vs. the randomized ustekinumab group (1·5 vs. 0·7; P < 0·001); greater proportions of patients in the guselkumab group achieved IGA 0/1 and at least a two‐grade improvement at week 28 (31·1% vs. 14·3%; P = 0·001) and week 52 (36·3% vs. 17·3%; P < 0·001). Greater proportions of patients treated with guselkumab achieved PASI 90, PASI 100 and DLQI 0/1 at week 52. After week 16, 64·4% of patients in the guselkumab group and 55·6% in the ustekinumab group had at least one adverse event (AE); infections were the most frequent AE type. Overall, 6·7% ( n = 9) of patients in the guselkumab group had at least one serious AE compared with 4·5% ( n = 6) for the ustekinumab group. Conclusions: Patients treated with ustekinumab who did not achieve an IGA of 0/1 by week 16 derived significant benefit from switching to guselkumab.